1995
DOI: 10.1152/ajpregu.1995.268.2.r487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-arginine-derived nitric oxide synthesis on neuronal activity in nucleus tractus solitarius

Abstract: The purpose of these studies was to determine the effects of L-arginine-derived nitric oxide (NO) synthesis on neuronal activity in solitary tract nucleus (NTS) neurons. Single unit activity was recorded extracellularly from medial NTS neurons in Fischer-344 rats in vivo and in vitro. In anesthetized rats with arterial pressure maintained constant, NG-nitro-L-arginine methyl ester (L-NAME, 10 mg/kg iv), an inhibitor of NO synthesis, decreased the discharge rate in 12 of 14 neurons and increased the discharge r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 0 publications
3
80
2
Order By: Relevance
“…53,54 NTS neuronal activity was reduced by systemic injection of L-NAME at constant blood pressure 55 while L-arginine and the NO donor, sodium nitroprusside (SNP) increased discharge rate. 56 The RVLM, the final site of sympathetic processing in the brainstem, also appears to contain neurons susceptible to an inhibitory influence by NO.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…53,54 NTS neuronal activity was reduced by systemic injection of L-NAME at constant blood pressure 55 while L-arginine and the NO donor, sodium nitroprusside (SNP) increased discharge rate. 56 The RVLM, the final site of sympathetic processing in the brainstem, also appears to contain neurons susceptible to an inhibitory influence by NO.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…Conversely, Chowdhary and Townend (28) have reported that NO serves to inhibit central sympathetic outflow and studies by Di Paola et al (29) show that the neurotransmitter L-glutamate which promotes the release of NO from nitrergic neurones stimulates, rather than inhibits, baroreflex processing within the NTS. Furthermore, singleneuron recordings within the NTS have shown reduced activity after systemic administration of L-NAME (30) and increased neuronal discharge after NO donors such as L-arginine and SNP (31). NO-mediated inhibition of the cardiac baroreflex appears not to be mediated at the level of the heart itself, since the available literature suggests that NO potentiates, rather than depresses, the magnitude of induced bradycardia (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…NO is linked to glutamatergic neurotransmission in the central nervous system (24,25) and activation of glutamate receptors in the nucleus tractus solitarius (NTS) and paragigantocellular nucleus is necessary to maintain normal levels of blood pressure and ventilation and also for a normal ventilatory CO 2 response to occur (26). It has been demonstrated that NO enhances the excitability and spontaneous discharge rates of neurons in the NTS (27) and may act as a retrograde messenger in an L-glutamate-releasing positive feedback system, also in the NTS, involved in the increase of ventilation during hypoxia (24). NO has an excitatory effect on the discharge rates of neurons in the pontine respiratory group, whereas L-NNA produces a disruption of the pneumotaxic mechanism (28).…”
Section: Discussionmentioning
confidence: 99%